Uma história social dos carnavais de Amargosa: modos de brincar e os “Cão”, 1940-1980 - Marques, Edicarla dos Santos (2010)
The carnivals in Amargosa between 1940 and 1980 were the focus of study in this work. An attempt to understand not only the city at your burlesque time and the many commemorative practices undertaken, but, above all, the relations, conflicts and dialogues, that were socially established and that in the carnival presented themselves an dilated way. Was also sought a shy conception of the history of the city, how a way to identify, identities, representations, as well the urban and festive dynamic. This work is a reflection of the social relations through the different kinds of the experimentation of the carnival, considering the factors of class, race and culture that marked these distinctions. Still exists a little bit of the condition of the woman from the study of their presence in the carnival. In this context also inserts itself a brief analysis of the practices of the “Cão”, spaces of circulations, identities and tensions related to these representatives of the festive religious imagery in Amargosa.